We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
124
1
avatar+814 

The quadratic \(-6x^2+36x+216\) can be written in the form \(a(x+b)^2+c\), where a, b, and c are constants. What is a+b+c?

 Aug 27, 2018
 #1
avatar
+1

First factor out a -6 to get \(-6(x^2-6x-36)\)

Then complete the square to get \(-6(x^2-6x+9)+270 ​​\) because 216+54=270

This simplifies to \(-6(x-3)^2+270\)

So \(a=-6\)\(b=-3\), and \(c=270\)  and \(a+b+c=-6+(-3)+270=261\)

.
 Aug 27, 2018

7 Online Users

avatar